What Drives Millenials and Y Generation Syaria to Perform at Start Up? - Intan Resty Indrasari; Mirwan Surya Perdhana (ITB AAS INDONESIA Surakarta, 2023)
This study aims to examine the factors that affect employee performance in millennial employees who work at start-up companies including factors related to the environment, work, and employees. Source of data used in this research is primary data. The data collection technique used the Google Gorm Questionnaire which was distributed via social media LinkedIn, WA, Instagram and Facebook. The questionnaire consisted of 40 question items which were measured using a Likert scale of 1-4 with levels of strongly disagree, disagree, agree, and strongly agree. Data analysis using SEM path analysis with Smart PLS. Of the 13 hypotheses proposed, four hypotheses were accepted, namely the effect of training on employee commitment, job autonomy on employee performance, and training on employee performance. Meanwhile, employee commitment does not mediate the influence of management support, organizational climate, job autonomy, and training on the performance of millennial employees working in start-ups.